Natural Killer Group 2, Member D/NKG2D Ligands in Hematopoietic Cell Transplantation - Carapito, Raphael; Aouadi, Ismail; Ilias, Wassila; Bahram, Seiamak (Frontiers in Immunology, 2017)
NKG2D is an invariant activatory receptor present on subsets of NK and T lymphocytes. It stimulates the cytolytic effector response upon engagement of its various stress-induced ligands (NKG2DL). Malignant transformation and conditioning treatment prior to hematopoietic cell transplantation (HCT) are stress factors leading to the activation of the NKG2D/NKG2DL signaling in clinical settings. In the context of HCT, NKG2D bearing cells can kill both tumor and healthy cells expressing NKG2DL. The NKG2D/NKG2DL engagement has therefore a key role in the regulation of one of the most salient issues in allogeneic HCT, i.e. maintaining a balance between graft-versus-leukemia (GVL) effect and graft-versus-host disease (GVHD). The present review summarizes the current state of our knowledge pertaining to the role of the NKG2D and NKG2DL in HCT.